The Volcanic Impacts on the Formation of Organic-Rich Shales From the Freshwater to Saline Lakes: Cases Study in the Ordos and the Junggar Basins - Wang, Xiaojun; Gao, Jiahong; Zhong, Liang; He, Wenjun; Jin, Zhijun; Zhu, Rukai; Liang, Xinping; Liu, Kouqi; Zhang, Wang (Frontiers in Earth Science, 2022)
High organic matter abundance is necessary for large-scale hydrocarbon accumulation and enrichment in shale oil. Comparing conventional marine basins with lacustrine ones, the formation of organic matter in the latter usually changes rapidly with strong heterogeneity, which brings great challenges to identify sweet spot prediction and resource evaluation. In addition, water columns with different redox conditions also affect the burial and preservation of organic matter during the deposition of lacustrine shales, especially under the impact of ephemeral critical geological events such as volcanic activities. Therefore, determining the properties and the influencing factors on the water columns is one of the key scientific issues in revealing the differential enrichment of organic matter in such basins. By comparing the petrological and geochemical characteristics of organic-rich shales between a typical freshwater and a saline lacustrine basin, this study analyzes the depositional environment and water column properties during the burial and preservation of organic matter in the Ordos and Junggar basins. The results demonstrate that volcanic activity intensifies the degree of hypoxia during the formation of organic-rich matter, which in turn affects organic matter preservation. The sulfate reduction index (SRI) indicates that the organic-rich shale of the Chang 7 Member (Ch7) of Yanchang Formation in the Ordos Basin and the Lucaogou Formation (P2l) in the Jimsar Sag of Junggar Basin in freshwater-saline environments have a certain intensity of sulfate reduction (BSR) (SRI < 1.375). The organic matter consumed by BSR is lower than the preserved organic matter, resulting a higher TOC content. However, excessive volcanic activity or the input of hydrothermal fluids caused strong BSR (SRI > 1.375) of the Fengcheng Formation (P2f) in saline lake of the Mahu Sag in Junggar Basin. This indicates that a large amount of organic matter was degraded and consumed, causing more iron oxides (and other iron-containing minerals) dissolve gradually to form pyrite, reducing the TOC content. This study enabled us to understand the shale oil enrichment, sweet spot prediction and evaluation, and propose a better theoretical and practical model for hydrocarbon accumulation in shale formations, to guide future exploration efforts.